Efficacy and safety of acupuncture for functional constipation: a randomised, sham-controlled pilot trial - Hye-Yoon Lee; Oh-Jin Kwon; Jung-Eun Kim; Mikyeong Kim; Ae-Ran Kim; Hyo-Ju Park; Jung-Hyo Cho; Joo-Hee Kim; Sun-Mi Choi (BMC, 2018)
Abstract Background The prevalence of functional constipation (FC) is 3-27%, and FC has been reported to cause discomfort in daily life and various complications. The treatment for FC depends on laxatives, and thus, effective and non-toxic alternative treatments are needed. Methods We conducted a randomised, sham-controlled parallel-design, pilot trial. Participants with FC were randomly assigned to either the real acupuncture (RA) or sham acupuncture (SA) group. The RA consisted of eight fixed acupuncture points (bilateral ST25, ST27, BL52 and BL25) and four additional points targeted to the individual based on Traditional Korean medicine (TKM). SA consisted of shallow acupuncture insertion at 12 non-acupuncture points. Twelve sessions were provided over 4 weeks. The outcome measures were weekly defecation frequency (DF), spontaneous complete bowel movement (SCBM), Bristol stool scale (BSS) score and constipation assessment scale (CAS) score. The participants were followed for 4 weeks after the treatment. Results Thirty participants were enrolled (15:15). The mean DF were 5.86 ± 5.62, 5.43 ± 3.39 and 5.79 ± 3.64 in the RA group and 3.73 ± 1.62, 5.00 ± 1.77 and 5.40 ± 1.96 in the SA group at weeks 1, 5, and 9, respectively. The increases in weekly SCBMs were 2.50 ± 3.86 and 2.71 ± 4.01 with RA and 2.33 ± 2.74 and 1.93 ± 2.25 with SA at weeks 5 and 9, respectively (mean difference [MD] 0.78). The BSS scores were 0.57 ± 1.72 and 1.09 ± 1.30 with RA and 0.15 ± 1.06 and 0.14 ± 0.88 with SA at weeks 5 and 9, respectively (MD 0.95). The CAS score changes were − 3.21 ± 2.91 and − 3.50 ± 3.98 with RA and − 2.67 + ±2.82 and − 2.87 ± 2.95 with SA at weeks 5 and 9, respectively. Greater improvements were observed in subgroup analysis of participants with hard stool. The numbers of participants who developed adverse events (AEs) were equal in both groups (four in each group), and the AEs were not directly related to the intervention. Conclusions This clinical trial shows feasibility with minor modifications to the primary outcome measure and comparator. Acupuncture showed clinically meaningful improvements in terms of SCBMs occurring more than 3 times per week and in these improvements being maintained for 4 weeks after treatment completion. As this is a pilot trial, future studies are warranted to confirm the efficacy and safety. Trial registration KCT0000926 (Registered on 14 November 2013).